Analysis of the Potential and Development of Natural Tourist Attractions at Telaga Cinta, Suli Village, Salahutu District, Central Maluku Regency - Samal, Rizki Rahmawati; Sihasale, Daniel Anthony; Leuwol, Ferdinand Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study aims to examine the tourism potential of the Telaga Cinta area in Suli Village and to identify strategies for developing the attraction's potential using a SWOT analysis. Telaga Cinta in Suli Village has several strengths, such as stunning natural lake scenery, attractive facilities, cleanliness and security, and basic infrastructure such as electricity and telephone networks for internet access. Additionally, the local community's hospitality is a distinctive attraction for tourists. However, some areas for improvement were addressed, including the poor condition of the road leading to the tourist site with several potholes and the lack of facilities for more food and beverage kiosks. Nevertheless, there are significant opportunities for the development of Telaga Cinta, such as job creation, increasing local community income, and the widespread availability of tourist information on the internet and social media. Regarding threats, Telaga Cinta faces several challenges, including more cooperation between the government and the community in developing the tourist site, competition from other tourist attractions, and improving facilities and services at competing tourist sites. SWOT analysis found that the intersection point lies, indicating the need to adopt a growth-oriented strategy focusing on improving transportation infrastructure and enhancing facilities according to visitor needs. Therefore, development efforts should focus on repairing the road to the location, providing the lacking facilities, and improving cooperation between the government and the local community.